In vitro Microtuber Induction and Regeneration of Plantlets from Microtuber Discs of Cultivated Potato (Solanum tuberosum L.) (Plant Tissue Culture and Biotechnology, 2019)
In vitro microtuber induction potential of a popular potato (Solanum tuberosum L.) variety Diamant was examined using different supplements of growth regulators. Results showed that MS supplemented with 4.0 mg/l BAP, 1.0 mg/l IAA and 1.0 mg/l GA3 produced the best response towards microtuber induction from in vitro raised stem cuttings. Further, these in vitro raised microtubers were used to establish a highly efficient shoot regeneration system. Highest number of regenerated shoots were obtained from the peripheral region of microtuber disc explant on the MS containing 4.0 mg/l BAP and 2.0 mg/l IAA. Histological analysis revealed that microtuber periderm was composed of a several layers of uniform meristematic phellogen cells which were responded to growth hormones in the above mentioned medium producing healthy multiple shoots. Effective roots developed from these in vitro raised shoots on half strength of MS with 0.2 mg/l IBA. The plantlets were eventually acclimatized in pots containing soil for their establishment.Plant Tissue Cult. & Biotech. 29(1): 63-72, 2019 (June)